A novel hinged ankle foot orthosis for gait performance in chronic hemiplegic stroke survivors: a feasibility study - Lee, Se-Han (Biomed Eng Lett, 2018)
Stroke survivors with gait disturbances may use ankle foot orthoses (AFOs). However, most AFOs come in one-piece styles, which make it difficult for spasticity-affected stroke survivors to don. AFOs are also limited since they do not properly prevent ankle joint for foot drop by itself. Therefore, the present study developed a novel hinged AFO by adding a locking device to a hinged joint. We then tested its feasibility in 9 hemiplegic stroke survivors by investigating temporal–spatial gait parameters using the GAITRite in the following 3 conditions: no AFO, traditional AFO, and novel hinged AFO. There was no significant difference in spatiotemporal gait parameters among the different conditions. There were greater decreases in gait velocity, cadence, step length, and stride length in the novel hinged AFO group than in the no AFO and traditional AFO groups. This novel hinged AFO was developed to prevent foot drop. However, the AFO did not show significant differences in gait parameters because it consists of metal with extra weight and volume. Functionally, it prevented foot drop. It also improved convenience by its releasable design. Thus, further studies are needed to develop an AFO that improves gait and is convenient to use for hemiplegic stroke survivors.